The Loyalty Role in Mediating Workload and Compensation for the Employee Performance at PT Pelindo IV (Persero) Cabang Terminal Petikemas Bitung - Miryam Theofilia Kolibu; Yustina Erti Pravitasmara Dewi (PT Mattawang Mediatama Solution, 2023)
This study aims to analyze the role of loyalty in mediating workload and compensation for Employee Performance at PT Pelindo IV (Persero) Cabang Terminal Petikemas Bitung. This study employed a quantitative approach. Respondents involved 170 employees of PT Pelindo IV (Persero) Cabang Terminal Petikemas Bitung. Data analysis used SmartPLS software. The research results show that three variables of workload, compensation and loyalty have provided significant influences. Workload has significant influences towards employee performance, loyalty, and employee performance through loyalty facilities at PT Pelindo IV (Persero) Cabang Terminal Petikemas Bitung. Then, there are significant influences of compensation towards employee performance, loyalty, and employee performance through loyalty at PT Pelindo IV (Persero) Cabang Terminal Petikemas Bitung.